Surface properties and hydrogen bonding of accelerator-free polyurethane dispersion/carboxylated nitrile butadiene rubber using crosslinker hybridisation - Ivy Gan; Wen Shyang Chow; Siong Hui Khoo; Mohamad Danial Shafiq (eXPRESS Polymer Letters, 2024)
This study focuses on producing polyurethane dispersion (PUD)/carboxylated nitrile butadiene rubber (XNBR) blends with different types of crosslinkers without both accelerators and sulphur. Two types of crosslinkers: epoxide crosslinker and organo-modified siloxane, are introduced in the PUD/XNBR (blending ratio of 80:20). The zeta potential and particle size of the PUD/XNBR blends were determined using a dynamic light-scattering nanoparticle analyser. The chemical interaction and surface roughness of the PUD/XNBR blends were evaluated using Fourier transform infrared spectroscopy (FTIR) and atomic force microscopy (AFM). The zeta potential and particle size of the PUD were influenced by XNBR blending and the types of crosslinkers. FTIR observations indicate that the XNBR and the crosslinkers facilitated intermolecular hydrogen bonding and different extents of ordered hydrogen bonding. A higher degree of ordered hydrogen bonding can be associated with a higher surface roughness of the PUD/XNBR blends. Nevertheless, the hybrid crosslinkers can be used to achieve reasonable surface roughness for the easier donning of latex gloves. The research findings can be applied to design glove products with desirable surface roughness and intermolecular bonding.